Contrastive Studies Hebrew-English. Specialised Bibliography C15. - British Council, London (England). English-Teaching Information Centre; British Council, London (England). English-Teaching Information Centre ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This selective bibliography lists 2 books, or sections in books, and 6 journal articles dealing with Hebrew-English contrastive studies. The entries range in date from 1965 to 1974. The books cited are Israeli or European publications, and the articles appeared in well-known European or American pedagogical language journals. (TL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Comparative Analysis; Contrastive Linguistics; English; English (Second Language); Error Patterns; Grammar; Hebrew; Interference (Language); Language Instruction; Reference Materials; Resource Materials; Second Language Learning; Syntax; Reference Materials, Bibliographies